2020
DOI: 10.1161/atvbaha.120.314383
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage (Drp1) Dynamin-Related Protein 1 Accelerates Intimal Thickening After Vascular Injury

Abstract: Objective: Mitochondria consistently change their morphology in a process regulated by proteins, including Drp1 (dynamin-related protein 1), a protein promoting mitochondrial fission. Drp1 is involved in the mechanisms underlying various cardiovascular diseases, such as myocardial ischemia/reperfusion injury, heart failure, and pulmonary arterial hypertension. However, its role in macrophages, which promote various vascular diseases, is poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…For example, M1-like macrophage polarization accompanies mitochondrial fragmentation, mitophagy, and decreased mitochondrial activity (34). Pharmacological inhibition of DRP1 or genetic deletion of Drp1, the key factor for the regulation of mitochondrial fission and mitophagy, blocks M1-like macrophage polarization (35,36). Moreover, increased production of mitochondrial ROS (mtROS) or accumulation of a mitochondrial metabolite, succinate, drives M1-like macrophage polarization by stabilizing hypoxia-inducible factor 1α (HIF-1α) (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…For example, M1-like macrophage polarization accompanies mitochondrial fragmentation, mitophagy, and decreased mitochondrial activity (34). Pharmacological inhibition of DRP1 or genetic deletion of Drp1, the key factor for the regulation of mitochondrial fission and mitophagy, blocks M1-like macrophage polarization (35,36). Moreover, increased production of mitochondrial ROS (mtROS) or accumulation of a mitochondrial metabolite, succinate, drives M1-like macrophage polarization by stabilizing hypoxia-inducible factor 1α (HIF-1α) (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that reperfusion-mediated energetic crises were attenuated by mitochondrial fission suppression in a mouse model of cardiac ischemia/reperfusion injury [67]. It was also reported that intimal thickening after coronary damage was enhanced by mitochondrial fission due to dysregulated macrophage function [68,69]. Further, it was demonstrated that inflammation and apoptosis of coronary endothelial cells were reduced via inhibition of mitochondrial fission or activation of mitophagy [70].…”
mentioning
confidence: 99%
“…In addition, gene ontology pathway analysis of upregulated genes in oxLDL-trained macrophages showed upregulation of pathways relevant to mitochondrial synthesis and function. It has previously been demonstrated that induction of mitochondrial fission in macrophages promotes atherosclerosis in mice [ 48 ], suggesting that alterations in mitochondrial fission might also be involved in the mitochondrial morphology changes in the current study. Moreover, stimulation of mitochondrial biogenesis could be (co)responsible for the observed increase in OXPHOS activity and mitochondrial size in oxLDL-trained macrophages.…”
Section: Discussionmentioning
confidence: 59%